Analisis Rasio Likuiditas, Solvabilitas Dan Profitabilitas Dalam Mengukur Kinerja Keuangan Pada Kantor Pusat KSP Kopdit Pintu Air Rotat - Matilde Angelina Passionista; Maria Nona Dince; Wihelmina M. Yulia Jaeng (Kajian Ekonomi dan Akuntansi Terapan, 2024)
This research aims to analyze the financial performance of KSP Kopdit Pintu Air Rotat in terms of analysis of liquidity ratios, solvency ratios and profitability ratios for the 2021-2023 financial year. The data analysis method used in this research is quantitative descriptive analysis using ratio analysis based on the Regulation of the Minister of Cooperatives and SMEs of the Republic of Indonesia Number 15 of 2021. The results of the research show that: Liquidity ratio with Current Ratio and Quick Ratio at KSP Kopdit Watergate Rotat for Financial Year 2021 -2023 in the “healthy” criteria. Meanwhile, the Cash Ratio calculation at KSP Kopdit Water Gate Rotat for the 2021-2023 financial year is in the "unhealthy" criteria. The solvency ratio value using the Debt To Asset Ratio calculation at KSP Kopdit Pintu Air Rotat for the 2021-2023 financial year continues to increase and is within the "healthy" criteria. Meanwhile, the calculation of the Debt To Equity Ratio at KSP Kopdit Pintu Air Rotat for the 2021-2023 financial year is in the "fairly healthy" criteria. The profitability ratio by calculating Return On Equity and Return On Assets at KSP Kopdit Pintu Air Rotat for the 2021-2023 financial year fluctuates and is within the "unhealthy" criteria.